Two Phase Secured Multiparty Sum Computation Protocol (2PSMC) for Privacy preserving data mining - Dr.T. Karthikeyan2, Selva Rathna1, (International Journal of Engineering and Computer Science, 2017)
Secured Multiparty Sum Computation is an important algorithm designed in Privacy preserving Data mining to perform aggregated computation on data distributed between multi parties. In this paper, a new protocol with an improved performance on complexity is designed to perform Secured Sum computation on Multiparty environment which will enable to develop better algorithms for Privacy preserving data mining process such as Classification, Clustering etc.